Intention to study digital marketing in the context of expected quality of a study program - Djokic, Ines; Milicevic, Nikola; Djokic, Nenad (Anali Ekonomskog fakulteta u Subotici, 2021)
Measuring the quality in higher education can be performed on a more general level, usually by adjusting the instruments for measuring the quality of services in general, or through instruments that are related most directly to the study program. In any case, in methodological terms, one should keep in mind the relevant scientific knowledge regarding the treatment of a model that describes the relations of quality and its dimensions. In addition to appropriate theoretical observations, a primary marketing research was conducted in this paper, in order to determine whether and to what extent the expected quality of the study program affects the intention to enrol in it. In this particular case, students of the Faculty of Economics in Subotica (n = 89) evaluated (in June 2021) the expected quality of the master study program Digital Marketing (which is to start at this faculty in the forthcoming academic) and expressed their intentions to enrol in that program. Structural equation modelling was used. The results indicate that the expected quality positively and statistically significantly affects the intention to study the study program. The construct of the expected quality itself is statistically significantly formed by the dimensions of quality in the following order (according to the strength of the impact): Generic Skills, Good Teaching, Clear Goals and Standards, Appropriate Workload, and Appropriate Assessment.